Awareness of Oral Cancer and OPMDs among Patients Attending the University Dental Hospital, Peradeniya, Sri Lanka - D. Somathunga, E. A. Shanika; H. Dissanayaka, D. M. Sithara; L. Ratnayake, D. R. Dilini; Jayasinghe, Ruwan D. (Asian Pacific Journal of Cancer Care, 2021)
Objective: To assess awareness of oral cancer and OPMDs among patients attending for dental treatment at the University Dental Hospital, Peradeniya. Methods and materials: A self-administered questionnaire was used to collect information from 500 randomly selected outpatients attended the University Dental Hospital, Peradeniya, Sri Lanka. The questionnaire included questions to ascertain information on socio-demographic parameters, awareness of oral cancer and OPMDs, habits of betel chewing, smoking and alcohol consumption. Results: 43.2% of the respondents were satisfactorily aware of the possibility of occurrence of oral cancer and OPMDs. From all the individuals who were participated to this questionnaire, 16 (3.2%) of individuals have a habit of betel chewing, 4.2% of individuals have a habit of smoking and 8.3% of individuals have a habit of alcohol consumption, respectively while having a satisfactory awareness about oral cancer and OPMDs. Conclusions: This survey revealed that most of the patients attending the hospital were not in a satisfied level of awareness about oral cancer and OPMDs. Knowledge about the causal relationships with betel chewing was low compared to tobacco smoking and alcohol consumption.